Strategies of Copyright Trading in Publising Groups in China. - Xin Liu (International Journal of the Book)
Statistics show that with the attendance of more than 900 publishers from over 40 countries of the world, 8250 copyrights agreements, which make a historical record, were reached between Chinese publishers and their overseas counterparts in 2004 Beijing International Book Fair. Taiwan has the highest number of the agreements, which is 1873(22.70% of the total). British publishers are the second with 1460 agreements signed (17.7% of the total), followed by US publishers of 861 agreements(22.70% of the total). Statistics also show that among publishing groups, China Publishing Group—composed of eight members of elite publishers in China, ranks the first, 690 agreements signed, followed by Shanghai, Guanxi, Jiangsu and Hunan, the other four powerful publishing groups of the country. The rapid increase of copyright trading volume symbolizes the booming development of publishing industry in China. There tends to be greater expansion in book market with further opening of publication, distribution and printing fields in accordance with China's commitments to the World Trade Organization. Publishing groups will play significant roles in the transition of China's publishing industry. It is also evident that the more foreign books introduced into China, the more flourishing the market will be, but there certainly will be less market share for original Chinese books due to the present publishing systems in China. At present, Chinese publishers are allocated different amounts of ISBNs according to their sizes. In a sense, ISBNs are the resources to the Chinese publishers. Once they increase the publishing of foreign books, some of their resources will be taken up, resulting in the shrinkage of local Chinese books. What are the strategic ways of copyright trading performed in publishing group, not by each individual publishing house? Does the increasing number of rights transactions really mean revenues or profits to the Chinese publishing houses? Why some bestselling foreign titles sell far from the expectation of the Chinese publishing houses? What are the positive and negative effects of copyright trading to mainland China book market in the long run? The research will be conducted with the focus on these and related issues.